PELATIHAN KETERAMPILAN BERKOMUNIKASI PADA PEREMPUAN DI PANTI SOSIAL REHABILITASI WANITA TUNA SOSIAL - Hamzah, Hamzah; Herfriady, Herfriady (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2020)
Communication skills training activities were carried out at the Indralaya Social Rehabilitation Center for Socially Disabled Women, Ogan Ilir Regency. The participants in the activity were all clients and this activity was supported by the institution. The training method used was socialization with several stages including the preparation stage, implementation stage, evaluation and follow-up. Communication training for women at the Social Rehabilitation Center for Socially Disabled Women had a major influence on improving participants' communication skills, both verbally and non-verbally, by combining theoretical and practical approaches. This program plays a role in building clients' self-confidence in conveying ideas and strengthening clients' social abilities in interacting with their social environment.